A new model of phase change process for thermal energy storage. (19th June 2018) - Xia, Qingchao; Chen, Yanhu; Yang, Canjun; Zhang, Tao; Zang, Yujia
Summary: Thermal energy can be converted into mechanical energy through the melting process of a phase change material (PCM). A PCM mixed with an insoluble liquid has higher energy converting efficiency during the whole melting process, where the massive microvacuum formed during the freezing process is filled by the insoluble liquid, which increases utilization of the volume change. The traditional theoretical model of the phase change process is unable to sufficiently describe the mixed PCM; therefore, a new model aimed at analyzing the characteristics of the volumetric change rate, as well as the freezing and melting times of the mixed PCM, is theoretically constructed. In this paper, the effective heat capacity method is used, and the effects of porosity are considered when the PCM is in the solid state. Comparisons of this model with the traditional model are carried out using both simulations and experiments for different pressures and geometric structures. Our results indicate that the introduced model has better accuracy when describing the phase change process of the pure PCM mixed with an insoluble liquid. Abstract : A new mathematical model describing the phase change process of a mixture composed by a phase change material and an insoluble liquid inside a horizontal cylindrical container is proposed. Effective heat capacity method concerning the effects of vacuum pores and pressure is introduced for the theoretical analysis of this model, including a series of experimental studies.